Can Fiscal Decentralization Strengthen Social Capital? (IMF Working Papers; Working Paper, 2000)
Countries where social and political institutions stimulate interpersonal trust, civic cooperation, and social cohesiveness tend to have more efficient governments, better governance systems, and faster growth. This paper provides cross-country evidence, based on a sample of developing and developed countries, that fiscal decentralization-the assignment of expenditure functions and revenue sources to lower levels of government-can boost social capital and therefore be integrated into second-generation reforms.